I survived : the shark attacks of 1916 - Ball, Georgia (I survived (Graphic novel series), 2020)
Presents a graphic novel based on real-life events that follows a young boy named Chet who is attacked by a shark in a creek in New Jersey in 1916. He tries to warn others, but no one believes him. After nearly dying to save his friends from the shark, the shark is finally caught. Includes additional facts, photographs, and sources of more information.